2016
DOI: 10.1038/srep26116
|View full text |Cite
|
Sign up to set email alerts
|

GRK5 Deficiency Leads to Selective Basal Forebrain Cholinergic Neuronal Vulnerability

Abstract: Why certain diseases primarily affect one specific neuronal subtype rather than another is a puzzle whose solution underlies the development of specific therapies. Selective basal forebrain cholinergic (BFC) neurodegeneration participates in cognitive impairment in Alzheimer’s disease (AD), yet the underlying mechanism remains elusive. Here, we report the first recapitulation of the selective BFC neuronal loss that is typical of human AD in a mouse model termed GAP. We created GAP mice by crossing Tg2576 mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…In line with these data, He at al. showed that GRK5 deficiency was also responsible for selective basal forebrain cholinergic neurodegeneration [ 79 ].…”
Section: Grk5 and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In line with these data, He at al. showed that GRK5 deficiency was also responsible for selective basal forebrain cholinergic neurodegeneration [ 79 ].…”
Section: Grk5 and Neurodegenerative Diseasesmentioning
confidence: 99%
“…G protein-coupled receptor kinase-5 (GRK5) is one of the seven GRK family members whose primary function is to desensitize G protein-coupled receptors (GPCRs), which is essential for the desensitization and internalization of M2/M4 receptors [ 5 ]. Reduced levels of membrane (functional) GRK5 increased soluble β-amyloid in vitro , and decreased GRK5 membrane localization occurs in vivo as well as in an AD transgenic model and postmortem human AD brain samples [ 6 , 7 ]. GRK5 dysfunction mediates the deleterious cycle between cholinergic hypofunction and tau hyperphosphorylation, leading to increased β-amyloid deposition in the hippocampus [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As aforementioned, the GRK5 deficiency also renders the mice more susceptible to Swedish APP-induced cognitive impairment [16]. In that study, the relevant mechanistic exploration revealed that the GRK5 deficiency causes selective cholinergic neuronal vulnerability and therefore renders the subjects more susceptible to damages induced by a variety of secondary insults, including excess Aß, free radicals, and others.…”
Section: Discussionmentioning
confidence: 88%
“…However, although it alone does not directly cause any impairment, it does worsen the damages induced or triggered by other insults. For example, in addition to the abovementioned study in which the homozygote GRK5KO worsened aging-induced cognitive impairment [18], we recently found that the heterozygote GRK5KO also worsened the cognitive impairment induced by over-expression of Swedish mutant APP in the GAP mice [16]. Therefore, although GRK5 deficiency alone does not directly cause detectable damage, it alters the subject's sensitivity and renders it more susceptible to the damages induced or triggered by other insults.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation